Hubungan kualitas pelayanan, physical evidence dan keputusan berkunjung : efek mediasi minat - Dahmiri Dahmiri; Sigit Indrawijaya (LPMP Imperium, 2022)
This study has a purpose: to analyze whether the decision to visit the Muaro Jambi Temple tourist attraction area is influenced by the service quality variable and physical evidence through the variable interest in the visit. As the research population in this study, it was determined that all visitors to the Muaro Jambi Temple tourism object during 2021. The number of research samples used was 100 respondents. The research approach uses a quantitative approach, while the research method is a survey. The data analysis used Partial Least Square (PLS). Before testing the data, the first thing to do is test the outer model, which includes validity and reliability tests. The results are that the quality of service affects the interest in visiting, the service to visitors affects the decision to visit, physical evidence affects a person's interest in visiting, and physical evidence affects the decision to visit. Interest affects the decision to pay a visit to the tourist attraction of the Muaro Temple area.